2019
DOI: 10.3390/su11195409
|View full text |Cite
|
Sign up to set email alerts
|

Improving Centrifugal Compressor Performance by Optimizing the Design of Impellers Using Genetic Algorithm and Computational Fluid Dynamics Methods

Abstract: It has always been important to study the development and improvement of the design of turbomachines, owing to the numerous uses of turbomachines and their high energy consumption. Accordingly, optimizing turbomachine performance is crucial for sustainable development. The design of impellers significantly affects the performance of centrifugal compressors. Numerous models and design methods proposed for this subject area, however, old and based on the 1D scheme. The present article developed a hybrid optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 31 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…From the perspective of the life cycle, the most numerous phases are monitoring [30][31][32][34][35][36][37]47] and manufacturing [27,[39][40][41]45,51]. In addition, there is currently a certain amount of research in the prediction [14,25,26,44,46] and design [27,38,42] phases, and many scholars are also concerned about the operation and maintenance [29,43,51] phase.…”
Section: Overview On Life Cycle Of Turbomachinery With Digital Twinmentioning
confidence: 99%
“…From the perspective of the life cycle, the most numerous phases are monitoring [30][31][32][34][35][36][37]47] and manufacturing [27,[39][40][41]45,51]. In addition, there is currently a certain amount of research in the prediction [14,25,26,44,46] and design [27,38,42] phases, and many scholars are also concerned about the operation and maintenance [29,43,51] phase.…”
Section: Overview On Life Cycle Of Turbomachinery With Digital Twinmentioning
confidence: 99%
“…This can be achieved by optimizing the hub and shroud control points in the Bezier polynomial. Omidi et al [32] presented a comparison study between trimmed compressor and base one as can be seen in Figure 5. The results showed that the trimmed compressor presented a higher isentropic efficiency compared to the base one, with a maximum difference of 2%.…”
Section: Variable Trim Compressormentioning
confidence: 99%
“…Four basic mechanical turbocompounding arrangements with individual particular advantages and disadvantages have been developed (Figure 19, reproduced from Baines [32]). In the first type, the engine shafts and turbocharger are directly linked (Figure 19a).…”
Section: Mechanical Turbocompoundingmentioning
confidence: 99%
“…Shahram Derakhshan and Derakhshan investigated the slurry flow in centrifugal pumps to obtain an efficient optimization procedure. KM Guleren optimized a centrifugal pump using genetic algorithms [20] coupled with CFD considering flow physics for different impeller-diffuser configurations modelled with the maximum pressure increase and minimum relative flow angle as two objective functions. The results showed a significant increase in the pressure at the design flow rate (15.5 %), and a decrease at larger flow rates in the first optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Total pressure is used at the inlet so that the computations may analyze the parameter of performance with the highest degree of accuracy. The diffuser and volute both remain stationary while the impeller turns with a rotational speed of 92,000 rev/min [20]. The results of nominal specifications of the compressor were inserted into Vista CCD, and its performance curves are monitored (Fig.…”
mentioning
confidence: 99%